2017
DOI: 10.4049/jimmunol.1700192
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Safety of CRAC Inhibitors in Human Rheumatoid Arthritis Xenograft Models

Abstract: Store-operated Ca release-activated Ca (CRAC) channels are involved in the pathogenesis of rheumatoid arthritis (RA) and have been studied as therapeutic targets in the management of RA. We investigated the efficacy and safety of CRAC inhibitors, including a neutralizing Ab (hCRACM1-IgG) and YM-58483, in the treatment of RA. Patient-derived T cell and B cell activity was suppressed by hCRACM1-IgG as well as YM-58483. Systemically constant, s.c. infused CRAC inhibitors showed anti-inflammatory activity in a hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Wang et al have shown that verapamil, a Ca 2+ channel inhibitor, antagonized TNF‐α‐mediated inflammation in collagen‐induced arthritis mice via the reduction of Ca 2+ (Wang et al, ). The blockade of store‐operated Ca 2+ release‐activated channels with the use of neutralizing antibodies can also effectively suppress the activity of T cells and B cells derived from RA patients (Liu et al, ). Intriguingly, ionomycin‐mediated Ca 2+ modulation enhanced the tensile properties of developing engineered articular cartilage (Natoli et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al have shown that verapamil, a Ca 2+ channel inhibitor, antagonized TNF‐α‐mediated inflammation in collagen‐induced arthritis mice via the reduction of Ca 2+ (Wang et al, ). The blockade of store‐operated Ca 2+ release‐activated channels with the use of neutralizing antibodies can also effectively suppress the activity of T cells and B cells derived from RA patients (Liu et al, ). Intriguingly, ionomycin‐mediated Ca 2+ modulation enhanced the tensile properties of developing engineered articular cartilage (Natoli et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular targets responsible for the celastrol-mediated antiarthritic effect have been identified (Cascao et al, 2012;Li et al, 2012;Li et al, 2013;Astry et al, 2015;Cascao, Fonseca, & Moita, 2017 (Wang et al, 2016). The blockade of store-operated Ca 2+ release-activated channels with the use of neutralizing antibodies can also effectively suppress the activity of T cells and B cells derived from RA patients (Liu et al, 2017). Intriguingly, ionomycin-mediated Ca 2+ modulation enhanced the tensile properties of developing engineered articular cartilage (Natoli et al, 2010).…”
Section: Celastrol Suppresses Aia In Rats Via Mobilization Of Ca 2+mentioning
confidence: 99%
“…Spleen-derived and peripheral blood-derived pan T cells obtained from SNA and sham mice were loaded with fura-2, and a Ca 2+ influx assay was performed. 17,18 The peak and initial rates of SOCE were assessed and measured by relative fluorescence units (340/380 nm) ( Figure 4A and 4B). In SNA mice, there was a 9.14% decrease in peak Ca 2+ influx and a 5.15% decrease in initial Ca 2+ influx rates in splenic T cells, and an 18.74% decrease in peak Ca 2+ influx and an 18.22% decrease in initial Ca 2+ influx rates in peripheral T cells compared with sham mice.…”
Section: Dysfunction Of T Cells In Sciatic Nerve Axotomy Micementioning
confidence: 99%
“…Peripheral blood, synovium, articular cartilage, and bone explants were obtained from RA patients who had undergone prosthetic replacement arthroplasty for therapeutic purposes. A murine xenograft RA model was established as previously described (Liu et al, 2017). Briefly, explants of synovium, articular cartilage, and bone obtained from RA patients were grafted onto the muscle at the level of the fourth to sixth lumbar vertebra of male NOD/ShiJic-scid (NOD/SCID) mice aged 6-10 weeks (CLEA Japan, Tokyo, Japan).…”
Section: Establishment Of a Xenograft Human Ra Modelmentioning
confidence: 99%